Promoting a New Economy for the Middle East and North Africa - Arezki, Rabah; Belhaj, Ferid; Shah, Parmesh (World Bank, Washington, DC, 2019)
Countries in the Middle East and North Africa (MENA) possess all the ingredients they need to leapfrog into the digital future. They have large, well-educated youth populations that have already adopted new digital and mobile technologies on a wide scale. They have a highly educated female population. That combination has immense potential to drive future growth and job creation. The question is whether the region can adapt to a new economic reality. Public spending, the region's historical engine of development, has reached its limit. Because the public sector can no longer absorb the swelling ranks of university graduates, the MENA region has one of the world's highest rates of youth unemployment. For a variety of reasons, many of them cultural, highly educated women stay home. The female labor participation rate is among the lowest in the world. The digital economy holds the promise of a new way forward, but it is still in its infancy, and young people face obstacles in putting technology to productive use. Although the internet and hand-held devices are ubiquitous throughout the region, they are currently used for accessing social media, rather than for launching new enterprises. But there are green shoots emerging. For example, the ride-hailing app Careem has grown from a start-up to a billion-dollar company, creating thousands of jobs in 80 cities in the MENA region and in Pakistan and Turkey. And new digital platforms are already connecting job seekers and employers, providing vocational training, and hosting start-up incubators. The challenge now is to create the conditions for these green shoots to grow and multiply. The first, essential step is for MENA countries to become "learning societies," a phrase coined by the Nobel laureate economist Joseph E. Stiglitz to describe countries in which shared knowledge leads to increased innovation. This, in turn, fosters development; and in the case of MENA, it could lead to the creation of a vibrant digital service economy. To get there, education systems must change. For the region's young people, the curriculum is more often a source of frustration than advancement. The concept of a "skills premium" — the difference in wages between skilled and unskilled workers—dictates that higher educational attainment should lead to higher compensation and more secure employment. Yet in the MENA region, the opposite has happened: university graduates are far more likely to be unemployed than are workers with only a basic education. Two factors work against the region's young people. First, schools are still geared toward channeling graduates into large public sectors, which means they place less emphasis on fields such as mathematics and science. Second, bloated public sectors are crowding out the private sector, which would otherwise be a larger provider of high-skill, high-wage jobs.